DINAMIKA BIROKRASI DAN PERLUNYA REFORMASI BIROKRASI LINGKUNGAN - I Wayan Wesna Astara (Public Inspiration : Jurnal Administrasi Publik, 2016)
Indonesian bureaucracy are in flux. Bureaucracy also can not be separated from the process of political activity. In political activity, the government bureaucracy often use a dual role. On the one hand, the bureaucratic administration role, and on the other hand, can play the role of practical politics, if not set out clearly in law. Government bureaucracy has a role congenital defects, namely as 'official royal disease'. Congenital defect in question is the existence of an opinion that the leadership of the bureaucracy felt it would add prestige, prestigious ruling if she has a lot of staff numbers, although no analysis of whether the number of staff able to work or not. Bureaucratic reform is needed to improve the condition. Reform of the bureaucracy is putting bureaucracy as a public servant with a laid back bureaucracy as an institution of public servants and entrepreneurial system. Bureaucratic positions should be filled by those professional and competence. In addition, the need for strengthening supervision of conspiracy between political institutions and the bureaucratic institutions. Bureaucracy as implementers of government activity to public administration practices with three components, namely the government / state, private, people, still require the presence of additional components, namely a moral component. This component is required to maintain the bureaucratic and political conspiracy.Moreover, the moral components necessary to implement a system of bureaucratic cultural behavior of Pancasila that the smooth running of the state administration, the breath, the style and behavior of Pancasila.Keywords : Bureaucracy reformation, Pancasila Bureaucracy , Public service.